Can the Fluorescence Quantum Yield Be Enhanced by Introducing the Benzene Ring to the Blue Fluorescent Protein Chromophore? (Journal of Atomic and Molecular Sciences, 2019)
The green fluorescent protein (GFP) has been widely used in biochemical and biological fields forits strong fluorescence emitting property. The effective fluorescence emitting property lies in itschromophore P-HBI. Compared with GFP, the low fluorescence quantum yield (0.2 vs. 0.8 of GFP) of the wildblue fluorescent protein (BFP) restrict its extensive applications. In order to enhance the fluorescentquantum yield of BFP, numerous attempts have been executed to modify the molecular configuration suchas introducing the intramolecular hydrogen bond (IHB) or benzene ring to the parent structure. In thepresent work, we employed the high-level quantum chemistry calculation method CASSCF to investigate theexcited state deactivation mechanism of 4-BFP, which is a newly synthesized BFP chromophore derivative byintroducing a benzene ring to the five-membered heterocycle attempting to increase the fluorescencequantum yield. By combination of the optimization of stable electronic structures, scanning of potentialenergy surfaces and construction of energy profile, we found that the fluorescent quantum yield could notbe enhanced for the 4-BFP molecule. One minimum energy conical intersection was located between the S1and S0 states, which could act as the gateway for the 4-BFP to funnel to the ground state by the internalconversion process. The current work could provide fundamental guide for further molecular structuremodification or improvement to enhance the fluorescent quantum yield of BFP analogues.